2014
DOI: 10.1589/rika.29.561
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristic of Muscle Activity of the Oblique Muscles during Lateral Weight Transfer in the Sitting Position

Abstract: Purpose] The purpose of this study was to clarify the activity of oblique muscles during the sitting.[Subjects] The subjects of this study were 7 healthy males, mean age of 30.9 years. [Methods] An electromyography telemetry system (MQ-8, KISSEI COMTEC) was used for the measurements, and fifteen electrodes were arranged over the left oblique muscle. We measured electromyograms of the oblique muscles during lateral weight transfer in the sitting position. [Results] No significant changes were shown by the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The RA, IO, MF and TrA muscle activities significantly increased on the contralateral side in contrast to that on the ipsilateral side. This result is similar to that of the past reports 16 ) . As the lateral load transfer during the TRT resulted in the trunk bending towards the contralateral side, which requires lift-up of the contralateral pelvis, it was inferred that the lumbar muscle activity increased on the contralateral side in contrast to that on the ipsilateral side.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The RA, IO, MF and TrA muscle activities significantly increased on the contralateral side in contrast to that on the ipsilateral side. This result is similar to that of the past reports 16 ) . As the lateral load transfer during the TRT resulted in the trunk bending towards the contralateral side, which requires lift-up of the contralateral pelvis, it was inferred that the lumbar muscle activity increased on the contralateral side in contrast to that on the ipsilateral side.…”
Section: Discussionsupporting
confidence: 93%
“…The result showed that the activity of the bilateral lumbar muscles significantly increased during the TRT in contrast to those measured in the sitting posture. Watanabe et al 16 ) reported that the activity of the ipsilateral side lumbar muscles is maintained, whereas, the activity of the contralateral lumbar muscles increases when a lateral load transfer is performed in the sitting position. The results of this study reveal that the ipsilateral side lumbar muscle activities also increase when the vertical load is applied in addition to the lateral load transfer in the sitting position.…”
Section: Discussionmentioning
confidence: 99%